Endophytic bacteria associated with Myristica fragrans Houtt: Improved media, bacterial population, preliminary characterization, and potential as antibacterials - MELDA YUNITA; MORGAN OHIWAL; CHRISLAVENA SHINTA DIRKS; ONY WIBRIYONO ANGKEJAYA; NOOR ANDRYAN ILSAN; SUKMAWATI SUKMAWATI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Yunita M, Ohiwal M, Dirks CS, Angkejaya OW, Ilsan NA, Sukmawati S. 2022. Endophytic bacteria associated with Myristica fragrans Houtt: Improved media, bacterial population, preliminary characterization, and potential as antibacterials. Biodiversitas 23: 4047-4054. We have investigated a similar study previously and only obtained 4 isolates that were able to inhibit pathogenic bacteria with a very small inhibition index (1.5 mm-3.4 mm) in NA media. Therefore, the current study was conducted by improving the NA media with the addition of 1% peptone and Myristica fragrans filtrate. The study aimed to evaluate the potential of endophytic bacteria as antibacterials in the modified NA media. Endophytic bacteria were isolated from 5 organs of M. fragrans and were grown on Nutrient Agar added with 1% peptone and M. fragrans filtrate. The total bacterial population was analyzed by the TPC method. Preliminary characterization consisted of macroscopic and microscopic observations. Antibacterial test was carried out by agar diffusion method. The total population of endophytic bacteria varied for all organs of M. fragrans, with the highest population was found in the seeds (1x105 CFU/gr), while the least was found in the pulp (9x103 CFU/gr). A total of 10 isolates were selected and preliminary characterization showed that endophytic bacteria had different macroscopic and microscopic characteristics. All isolates were able to inhibit the growth of Escherichia coli ATCC-27853 and Staphylococcus aureus ATCC-29213 with the largest inhibition zone index was obtained by isolate BJ1 (22.5 mm and 23.8 mm), while the smallest was obtained by isolate TD2 (12.5 mm and 13.6 mm) which were still categorized as strong inhibition. The study concluded that the addition of 1% peptone and M. fragrans filtrate in NA media was able to show far better results compared to our previous study and the strong antibacterials can be developed and formulated in the future.